IS THERE ANY RELATIONSHIP BETWEEN THE TYPE OF DIETARY FAT AND BLOOD GLUCOSE? RESULTS OF ISFAHAN HEALTHY HEART PROGRAM - Niloofar Ghaderian; Noushin Mohammadi Fard; Firoozeh Sajjadi; Gholam Hosein Sadri; Ali Moattarian; Maryam Maghroon (ARYA Atherosclerosis, 2010)
Abstract INTRODUCTION: Existing evidence suggests that the type of dietary fat may affect glucose metabolism in the body. The objective of this study was to evaluate the relationship between the type of dietary fat and blood glucose. METHODS: This is a cross-sectional descriptive study of 12600 adults aged over 19 years who came from the provincial towns of Isfahan, Najaf Abad in Isfahan Province and Arak, Iran. The subjects were selected using the randomized-cluster sampling method. A food frequency questionnaire was used to obtain data on the subjects' dietary patterns. RESULTS: A significant positive relationship was observed in Arak between fasting blood sugar and the consumption of foods containing poly unsaturated fatty acids (PUFA) (P=0.04). There was a significant positive relationship in all three provincial towns between age and fasting blood sugar, 2-hour post-load plasma glucose (2HPP), body mass index (BMI), wais-to-hip ratio and waist circumference (P<0.001). There was a significant negative relationship between the male sex and all variables, except fasting blood sugar (P<0.001). Consumption of foods containing PUFA was found to have a significant positive relationship with body mass index (P=0.002) and waist circumference (P<0.001) in Isfahan; also in Najaf Abad there was a significant positive relationship between body mass index and consumption of PUFA sources (P=0.047). In Arak body mass index and waist circumference had positive relationship with consumption of PUFA sources (P<0.001). In all three provincial towns, diabetic patients had healthier dietary patterns compared to non-diabetics, in terms of the type of dietary fat. CONCLUSION: It can be concluded that the people's nutritional knowledge about dietary fats is inadequate. Hence Isfahan Healthy Heart Program can increase public awareness of the importance of disease prevention via appropriate interventions. Keywords: Dietary fat, Blood glucose, Fatty acids, Community Study.